Incubation as a type-scene in the Aqhatu, Kirta, and Hannah storie s a form-critical and narratological study of KTU 1.14 I-1.15 III, 1.17 I-II, and 1 Samuel 1:1-2:11 - Kim, Koowon. (Vetus Testamentum, Supplements, 2011)
Prior studies of incubation have approached it from a history of religions perspective, with a view to historically reconstruct the actual practice of incubation in ancient Near East. However, this approach has proven unfruitful, not due to the dearth of relevant data, but because of the confusion with regard to the definition of the term incubation. Suggesting a way out of this impasse in previous scholarship, this book proposes to read the so-called "incubation" texts from the perspective of incubation as a literary device, namely, as a type-scene. It applies Nagler's definition of a type-scene to a literary analysis of two Ugaritic mythical texts, the Aqhatu and Kirta stories, and one biblical story, the Hannah story.